Humble women, powerful nuns: a female struggle for autonomy in a men's church - Suenens, Kristien (KADOC studies on religion, culture and society, 2020)
Introduction -- Part I. Religious revival, Romanticism and female action in a post-revolutionary age: four young women (ca. 1820-1860) -- Part II. Female agency at a turning point: four congregation founders (1857-1867) -- part III. Female entrepreneurship and leadership in al ultramontane church: four convent superiors (ca. 1865-ca. 1885) -- Epilogue. The shaping of perceptions -- Conclusion. A study in ambiguity.